The Needs for Multicultural Knowledge in Instructional Material on Theme 7 "Beautiful Diversity in My Country" Grade 4th Elementary School - Diantini, Sam Isnar; Usodo, Budi; Soegiyanto, H. (Journal of Techno-Social, 2018)
The aims of research consist of the following (1) to know need analysis of Curriculum 2013 instructional materials in elementary school (2) to develop instructional material based on multicultural values. The study employs descriptive qualitative method which the data are collected by interview, observation, and document analysis. The observation and interview results about instructional materials of Curriculum 2013 in some elementary school in Surakarta consist of the following (1) teachers need additional materials in order to deliver suitable material of Curriculum 2013 for students. (2) Teachers get difficulties in selecting suitable additional material. (3) Teachers need additional material which can develop students good characters by adding Indonesian multicultural knowledge in all subjects. By enriching and developing multicultural values for students so it can be integrated in instructional materials such as tolerance, nationalism, and spirit of unity in diversities.